THE EFFECT OF BRAND AWARENESS, BRAND IMAGE AND ELECTRONIC WORD OF MOUTH ON PURCHASE INTENTION AZARINE SUNSCREEN PRODUCTS ON THE SHOPEE PLATFORM (STUDY ON TEENAGERS IN LHOKSEUMAWE CITY) - Syfa Ayu Ningrum; Jullimursyida; Muchsin; Halida Bahri (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This study aims to examine the effect of brand awareness, brand image and electronic word of mouth on purchase intention Azarine sunscreen products on the Shopee platform (study on teenagers in Lhokseumawe City). The population used is the people of Lhokseumawe City, especially teenagers who have never bought Azarine sunscreen products on the Shopee platform with a purposive sampling method with a sample size of 100 respondents. The data collection technique used in this study used the survey method. The data analysis method uses Multiple Linear Regression analysis. The results of this study found that brand awareness, brand image and electronic word of mouth were proven to have a positive and significant effect on purchase intention Azarine sunscreen products on the Shopee platform in Lhokseumawe City. Brand awareness has the most dominant influence, followed by brand image and electronic word of mouth. These findings indicate the importance of marketing strategies that focus on increasing brand awareness, positive brand image, and effective use of electronic word of mouth to increase the purchase intention Azarine sunscreen products among Lhokseumawe teenagers. This research is expected to contribute to companies in designing more effective marketing strategies.